TECHNICAL, COST AND ALLOCATIVE EFFICIENCY OF RICE, CORN AND SOYBEAN FARMING IN INDONESIA: DATA ENVELOPMENT ANALYSIS APPROACH - Rosihan Asmara (Socio-Economics/Agribusiness Department, 2017)
This study focuses on analyzing technical, cost and allocative efficiency and analyzing the influence of factors to the efficiency farming. The crops chosen for the analysis are rice, corn and soybean. The locations of this study are Jember, Banyuwangi, and Tuban Regency, East Java, Indonesia. The efficiency is measured using Data Envelopment Analysis (DEA). The results showed that the average technical efficiency for rice, corn, and soybean are 0.68, 0.73, and 0.81, respectively. Additionally, cost efficiency are 0.10, 0.12, and 4.55 for rice farming, corn farming, and soybean farming, respectively. This described that improving the efficiency of food farming in Indonesia is imperative. Accordingly, the most dominant factors affecting the technical (TE) and cost (CE) efficiency in rice, corn and soybean farming are land area and extension frequency. Therefore, the policies regarding land management and extension program should become the main attention of government. The program should be performed to address the local problem of production and also marketing of agriculture products in such a way that result in increasing profit and welfare of farmers.